2019
DOI: 10.1136/neurintsurg-2019-015113
|View full text |Cite
|
Sign up to set email alerts
|

Direct thromboaspiration efficacy for mechanical thrombectomy is related to the angle of interaction between the aspiration catheter and the clot

Abstract: BackgroundDirect thromboaspiration has been reported as an effective mechanical treatment for acute ischemic stroke. We aimed to determine whether the angle of interaction between the aspiration catheter and the clot affects the success of clot removal in ischemic stroke patients with large vessel occlusion in the anterior and posterior circulation.MethodsAll patients treated at our institution by direct thromboaspiration as a firstline technique between January 2016 and December 2017 were enrolled in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 36 publications
1
57
2
Order By: Relevance
“… 23 For example, it has been shown that the vascular architecture adjacent to the clot (ie, the angle of interaction between the thrombectomy material and the clot) is associated with successful thromboaspiration. 16 In our study, we showed that some thrombus parameters are predictive of first-attempt recanalization following thromboaspiration, as well as the overall difficulty of thrombus removal. As the RFs include information on the shape of the clot, these may have contributed to the good prediction observed in the validation cohort.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“… 23 For example, it has been shown that the vascular architecture adjacent to the clot (ie, the angle of interaction between the thrombectomy material and the clot) is associated with successful thromboaspiration. 16 In our study, we showed that some thrombus parameters are predictive of first-attempt recanalization following thromboaspiration, as well as the overall difficulty of thrombus removal. As the RFs include information on the shape of the clot, these may have contributed to the good prediction observed in the validation cohort.…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown recently that vessel architecture at the occlusion site in the form of the angle of interaction between the aspiration catheter and the clot was associated with successful recanalization. 16 Another recent study also reported that the texture of the clot, or radiomic features (RFs), is predictive of recanalization following treatment with intravenous alteplase for AIS. 17 This suggests that the extraction of pretherapeutic RF from radiological imaging may contain valuable information related to the composition of the clot, with an impact on the future success of MTB.…”
mentioning
confidence: 99%
“…Intracranial tortuosity hinders the performance of both SR and CA techniques. Bernava et al 58 recently established that an angle of interaction between the aspiration catheter and clot of ≥125.5° as a significant predictor of successful clot retrieval. As such, in face of severe intracranial tortuosity, it may be advantageous to place the CA catheter more distally to achieve a position as close to the same axis of the occlusive clot as possible to optimize the retrieval force.…”
Section: Unfavorable Vascular Anatomy In Intracranial Arteriesmentioning
confidence: 99%
“…Significant intracranial tortuosity distal to the carotid siphon is another critical factor that reduces MT effectiveness; in particular, increased curvature of the carotid T and the MCA M1 and M2 segments impairs clot removal with MT using SR or CA. [55][56][57][58] As a general rule, when intracranial vessel anatomy is deemed to be unfavorable, especially in the setting of a curved MCA or tortuous basilar artery, we tend to use CA either alone or in combination with SR. In case of failure or if an aspiration catheter is not available, another rescue therapy is the use of double parallel SRs to increase the force during the retrieval maneuver.…”
Section: Beyond the Carotid Siphonmentioning
confidence: 99%
See 1 more Smart Citation